Partisipasi Masyarakat Dalam Program Kampung Tangguh Semeru Wani Jogo Suroboyo Di Rt 06 Dan Rt 07 Rw 02 Kelurahan Keputih Kota Surabaya - Farras Ar Rasyid , Muhammad Lazuardi; Hertati, M. Si , Dr. Diana (Institut Riset dan Pengembangan Indonesia, 2023)
This research is based on the phenomenon of the government program Kampung Tangguh Semeru Wani Jogo Suroboyo in RT 06 and RT 07 RW 02 Keputih Village, Surabaya City, which won 1st place in the Kampung Tangguh Semeru Wani Jogo Suroboyo Period V Competition by the Surabaya City Government and Surabaya City Police. The purpose of this study was to determine and describe community participation through the Kampung Tangguh Wani Jogo Suroboyo program in RT 06 and 07 RW 02 Keputih Village, Surabaya City. This type of research is descriptive qualitative using data collection techniques, namely observation, interviews, and documentation. This research was conducted in RT 06 and RT 07 RW 02 Keputih Village, Surabaya City. This research refers to updating the information obtained from the situation in the field by referring to the theory of Forms of Community Participation according to Huraerah. In this case there are five study targets, namely: (1) Ideast Participation; (2) Labor Participation; (3) Property Participation; (4) Skills and Proficiency Participation; (5) Social Participation. The research results obtained are: 1) In terms of participation of Ideas, it can be stated that it is good; 2) In terms of labor participation, it can be stated that it is good; 3) In terms of property participation, it can be stated that it is good; 4) In terms of participation of skills and skills, it can be stated that it is good; 5) In terms of social participation, it can be stated that it is good.